2010
DOI: 10.1007/s10404-010-0655-7
|View full text |Cite
|
Sign up to set email alerts
|

Thin film evaporation in microchannels with interfacial slip

Abstract: We investigate the role of interfacial slip on evaporation of a thin liquid film in a microfluidic channel. The effective slip mechanism is attributed to the formation of a depleted layer adhering to the substrate-fluid interface, either in a continuum or in a rarefied gas regime, as a consequence of intricate hydrophobic interactions in the narrow confinement. We appeal to the fundamental principles of conservation in relating the evaporation mechanisms with fluid flow and heat transfer over interfacial scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The liquid velocity slip arises from the less effective momentum transfer between the wall and liquid molecules when the liquid does not completely wet the wall. The momentum deficit is due to the imbalance between the wall adhesion force and the shear force, especially when the liquid is depleted near the wall [4,14,20]. Similarly, the temperature slip and the Kapitza resistance arise because the solid-liquid heat transfer is less efficient than the solid-solid heat transfer when the solid-liquid interactions are weak.…”
Section: Solid-liquid Interface Region and Velocity Slipmentioning
confidence: 96%
See 3 more Smart Citations
“…The liquid velocity slip arises from the less effective momentum transfer between the wall and liquid molecules when the liquid does not completely wet the wall. The momentum deficit is due to the imbalance between the wall adhesion force and the shear force, especially when the liquid is depleted near the wall [4,14,20]. Similarly, the temperature slip and the Kapitza resistance arise because the solid-liquid heat transfer is less efficient than the solid-solid heat transfer when the solid-liquid interactions are weak.…”
Section: Solid-liquid Interface Region and Velocity Slipmentioning
confidence: 96%
“…The bulk liquid and the liquid in the interface region have different physical properties. The liquid in the nanolayer as shown in Figures 1-3 is (1) more ordered and stratified than the bulk liquid because it is adsorbed on the wall with a crystalline or semi-solid structure for the wetting case [5] or is (2) sparse and disordered like a rarefied gas for the extremely nonwetting case [14] and is (3) mobile and flowing with an intrinsic slip velocity, u w , at the wall surface for both cases. The density, viscosity, and thermal conductivity of the nanolayer continuously decrease with increased surface hydrophobicity.…”
Section: Solid-liquid Interface Region and Velocity Slipmentioning
confidence: 98%
See 2 more Smart Citations
“…This work gave the relationship of heat flow in terms of the contact angle, superheat and material properties and can also be applied to different tube geometries. Recently, Biswal et al [12] studied the impact of including interfacial slip in the evaporation of thin-film. Based on their semi-analytical solution, it was concluded that the interfacial slip thickens the liquid film, which in turn lowers the mass transfer from the thin-film to the vapour phase.…”
Section: Introductionmentioning
confidence: 99%